Reflexiones sobre la crisis financiera - Anicama Pescorán, Juan (2009)
It is a virtual participation in a recent congress on financial globalization, linked to this global environment, that motivates this article to analyze and interpret what is happening in the economy plunged into a serious crisis, which in essence is beyond the financial environment; progress in the exposure of some of its features, almost hand passing of the crisis.